Statistical-Economic Design of Control Chart If The Vector of Target Values of Multi-Variables Shifts With Time - Hong Mao; Jin Wang (Randwick International of Social Science Journal, 2021)
In this paper, the statistical-economic design of a multivariate special triangle control chart is proposed to control the processes of the quality characteristics or financial indices shifting with time. A multi-objective programming with several constraints is used to determine optimal solutions of control region (probability of false alarm), the power of finding out assignable cause(s), sample interval and sample size. An application of the statistical-economic design of a Multivariate special triangle control chart is illustrated to control the soundness of insurers of U.S